Persistent increase of β‐hCG level after salpingectomy in tubal pregnancy: Good or bad news?. Issue 4 (11th March 2021) - Pinto Ribeiro, Pedro Cristiano; Amann, Niklas; Alba Alejandre, Irene; Kost, Bernd; Mahner, Sven; Kaltofen, Till
Abstract: Heterotopic pregnancy is a rare event in natural conception (1:30000). We describe a case of a 36‐year‐old nulliparous. She presented to our department in the 4 + 6 gestational week with two simultaneous pregnancies intrauterine and extrauterine. Here, we compare treatment options and ultrasound findings to help examiners avoid inadequate therapeutic approaches. Abstract : Examiners should take extra care when performing the ultrasound in all women of reproductive age with clinical symptoms, because once a EUP is detected, clinicians tend to forget the possibility of a coexisting intrauterine pregnancy.